Natural Polymers Based Hydrogels for Cell Culture Applications - Jose, Gils; Shalumon, K.T.; Chen, Jyh-Ping (Current Medicinal Chemistry, 2020)
It is well known that the extracellular matrix (ECM) plays a vital role in the growth, survival and differentiation of cells. Though two-dimensional (2D) materials are generally used as substrates for the standard in vitro experiments, their mechanical, structural, and compositional characteristics can alter cell functions drastically. Many scientists reported that cells behave more natively when cultured in three-dimensional (3D) environments than on 2D substrates, due to the more in vivo-like 3D cell culture environment that can better mimic the biochemical and mechanical properties of the ECM. In this regard, water-swollen network polymer-based materials called hydrogels are highly attractive for developing 3D ECM analogs due to their biocompatibility and hydrophilicity. Since hydrogels can be tuned and altered systematically, these materials can function actively in a defined culture medium to support long-term self-renewal of various cells. The physico-chemical and biological properties of the materials used for developing hydrogel should be tunable in accordance with culture needs. Various types of hydrogels derived either from natural or synthetic origins are currently being used for cell culture applications. In this review, we present an overview of various hydrogels based on natural polymers that can be used for cell culture, irrespective of types of applications. We also explain how each hydrogel is made, its source, pros and cons in biological applications with a special focus on regenerative engineering.
Keywords: Hydrogels